A system to monitor a portion of the total testing process in medical clinics and laboratories: feasibility of a split-specimen design - Shahangian, S; Krolak, J M; Gaunt, E E; Cohn, R D (Archives of pathology & laboratory medicine (1976), 1998)
The purpose of this study was to assess the feasibility of using a prototype split-specimen design to assess integrity of a portion of the total testing process in medical clinics and laboratories. Two or three tubes of venous blood were collected from 177 patients for analysis of one of three analytes (serum potassium, serum total cholesterol, and whole-blood hemoglobin). Patients were seen at one of the nine clinics participating in this study. In all cases, one tube of blood from each patient was sent to a commercial referral laboratory, and the other tube(s) forwarded to the laboratory that routinely tested specimens for the clinic (participating laboratory) for analysis. Each participating laboratory removed a preanalysis and sometimes a post-analysis aliquot from each specimen and forwarded these to the referral laboratory for analysis. The study was conducted in six physician office laboratories (three serving 1 to 4 [mean, 2.7] internists and three serving 3 to 24 [mean, 12] family physicians) and three hospital laboratories (serving hospitals with 100 to more than 700 beds). Study patients were voluntary participants and provided informed consent. Patient age ranged from 18 to 80 years, and for all the laboratory test was specifically ordered for clinical reasons. Patients who were unable or unwilling to provide informed consent, those for whom testing would require that they provide more than 100 mL of blood, those whose blood was being collected by fingerstick, and those with results that were part of a laboratory test profile were excluded. Two main outcome measures were assessed: (1) percent differences between split-specimen results exceeding the maximum allowable imprecision level, which was based on published biological variation data (defined as one-half of the intraindividual percent coefficient of variation), for each analyte (result discrepancies); and (2) all "problems" (defined as departures from standard operating procedures) that could be documented by retrospective review of all relevant medical and laboratory records. The rate of result discrepancies was 1 in 20 (5%) for patients in whom hemoglobin was analyzed, 12 in 57 (21%) for patients in whom potassium was analyzed, and 1 in 60 (2%) for patients in whom total cholesterol was analyzed. Results of samples obtained during the aliquoting and storage phases of the total testing process were subject to study-induced problems and were generally not useful in tracing problems to specific stages of the testing process. A total of 28 problems (involving 26 patients) were documented, but only 6 problems were due to routine testing processes. The feasibility and limitations of a split-specimen design to detect result discrepancies were demonstrated. Most documented problems (22 of 28, or 79%) were study induced. To assess integrity of the total testing process, such problems need to be avoided.